We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
451
2
avatar+267 

\(x^2 -2x + 3 - 2i\sqrt{3} =0\)

 

Hello! How would I go about solving this particular equation? Factoring this seemed awful, I tried factoring out sqrt(3) out of 3 and 2i*sqrt(3) but ended up with nothing useful since the i is still there. Using the quadratic formula gave me a complex number in the root sign and I'm not sure how to handle that. What about if the x^2 had a i attached to it? So this one for instance:

 

\(ix^2 -2x + 3 - 2i\sqrt{3} =0\)

 

Thanks!

 Oct 12, 2017
 #1
avatar+100569 
+1

x^2  + 2x  +  3  -2i√3  = 0          rearrange as

 

x^2  +  2x   =   -3 + 2i√3           

 

Take   1/2 the coefficient on x = 1......square it  = 1   and add to both sides

 

x^2 + 2x + 1  =  -3  + 2i√3  + 1       factor the left side....simplify the right side

 

( x + 1)^2  = -2 + 2i√3   factor the right side

 

(x + 1)^2   =  2 (i√3 - 1)     take both roots

 

x + 1  =  ±√ [ 2  (i√3 - 1) ]     subtract 1 from both sides

 

x  =    ±√ [ 2  (i√3 - 1) ]  -   1

 

 

cool cool cool

 Oct 12, 2017
 #2
avatar+267 
0

Oh... is there no way to simplify that? It seems like a very messy answer. How about the second case with an i coefficient infront of the x^2 term? thanks

Quazars  Oct 13, 2017

7 Online Users

avatar